2016
DOI: 10.3847/0004-637x/832/1/93
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-Darkened Seasons: Insolation Around Rapid Rotators

Abstract: I model the effect of rapid stellar rotation on a planet's insolation. Fast-rotating stars have induced pole-to-equator temperature gradients (known as gravity-darkening) of up to several thousand Kelvin that affect the star's luminosity and peak emission wavelength as a function of latitude. When orbiting such a star, a planet's annual insolation can strongly vary depending on its orbit inclination. Specifically, inclined orbits result in temporary exposure to the star's hotter poles. I find that gravity-dark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…From the gravity darkening and oblateness modeling in Ahlers et al (2020a), we produced an effective temperature map of the host star and generated the total irradiance I experienced by KELT-9b as a function of orbital phase, using the model described in Ahlers (2016). The equilibrium dayside temperature of KELT-9b is related to the incident irradiance via T day ∝I 1/4 , and we computed the relative change in thermal emission from the planet associated with the varying dayside temperature (see the numerator in the first term of Equation (9)).…”
Section: Consequences Of Rapid Stellar Rotation and Kelt-9b's Polar Omentioning
confidence: 99%
“…From the gravity darkening and oblateness modeling in Ahlers et al (2020a), we produced an effective temperature map of the host star and generated the total irradiance I experienced by KELT-9b as a function of orbital phase, using the model described in Ahlers (2016). The equilibrium dayside temperature of KELT-9b is related to the incident irradiance via T day ∝I 1/4 , and we computed the relative change in thermal emission from the planet associated with the varying dayside temperature (see the numerator in the first term of Equation (9)).…”
Section: Consequences Of Rapid Stellar Rotation and Kelt-9b's Polar Omentioning
confidence: 99%
“…Additionally, the star's abundant centrifugal force near its equator distorts its hydrostatic equilibrium, causing its effective temperature to vary by nearly a thousand Kelvin over the surface of the star. These two effects of stellar oblateness and varying effective temperature -together commonly referred to as gravity darkening (Barnes 2009)-change the total irradiance on KELT-9 b (Ahlers 2016). The star's oblateness changes the overall shape and size of the projected disk in the sky that KELT-9 b sees depending on its location in the system, and the star's decreased temperature decreases output stellar radiation near its equator.…”
Section: Introductionmentioning
confidence: 99%
“…4 via Doppler tomography, meaning KELT-9 b resides in a polar orbital configuration. Therefore, KELT-9 b varies in exposure to the host star's hotter poles and cooler equator, which has been shown to significantly impact a planet's total irradiation in similar systems (Ahlers 2016;Ahlers et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observing programs such as the Kepler mission have demonstrated that stellar variability in high mass stars often renders transit light curves unusable . Additionally, high-mass stars often rotate rapidly, inducing an oblate shape and a pole-to-equator luminosity gradient across the stellar surface ; Ahlers 2016). These two effects add challenges to traditional light curve analysis, radial velocity measurements, Doppler tomography, and Rossiter McLaughlin measurements (Gimenez 2006;.…”
Section: Introductionmentioning
confidence: 99%